Precision surgery for obsessive compulsive disorder—which is the proper target? - Barcia, Juan Antonio; Reneses, Blanca; Nombela, Cristina (Annals of Translational Medicine, 2019)
Obsessive-compulsive disorder (OCD) is a mental health condition in which recurring, anxiety-inducing thoughts or urges (obsessions) are usually followed by uncontrolled mental or behavioral acts (compulsions) being the cause of major illness related disability (1). Patients diagnosed with OCD resistant to medical and psychiatrical treatment may be contemplated for surgery.